Factors Determining Dividend Payment Policy: Further Evidence from Financial Sector Companies on the Indonesia Stock Exchange - Ahsanal Huda; Muhammad Iqbal; Wan Ruslan Abdul Ghani (Danadyaksa: Post Modern Economy Journal, 2026)
Dividend policy in the banking sector plays a strategic role because it is related to financial stability, investor confidence, capital adequacy, and the sustainability of the intermediation function. This study examines profitability, leverage, free cash flow, and firm size as determinants of dividend policy in banks listed on the Indonesia Stock Exchange. This study uses an associative quantitative approach with secondary panel data obtained from the Indonesia Stock Exchange for the period 2006 to 2025, covering six banks and 120 observations. The analysis was conducted using EViews 12 through panel data regression with the selected Random Effect Model. The results show that profitability and firm size have a positive and significant effect on dividend policy, while leverage and free cash flow have no significant effect. This finding confirms that a bank's ability to generate profits and total asset strength are the main factors in driving dividend payments, while funding structure and cash availability are not yet dominant determinants because bank dividend policy is influenced by prudential regulations, capital adequacy, liquidity risk, and the need to maintain financial stability. This study's theoretical contribution strengthens Signaling Theory and Resource-Based View Theory through evidence that profitability and firm size act as financial signals and strategic internal resources in supporting dividend policy. The empirical contribution of this study extends the dividend policy literature in the financial sector by confirming that the determinants of bank dividends are different from those in the non-financial sector.